Risk Factors for Atonic Postpartum Hemorrhage: A Systematic Review and Meta-analysis - Ende, Holly B; Lozada, M James; Chestnut, David H; Osmundson, Sarah S; Walden, Rachel L; Shotwell, Matthew S; Bauchat, Jeanette R (Obstetrics and gynecology (New York. 1953), 2021)
To identify and quantify risk factors for atonic postpartum hemorrhage. PubMed, CINAHL, EMBASE, Web of Science, and and ClinicalTrials.gov databases were searched for English language studies with no restrictions on date or location. Studies included randomized trials, prospective or retrospective cohort studies, and case-control studies of pregnant patients who developed atonic postpartum hemorrhage and reported at least one risk factor. Title, abstract, and full-text screening were performed using the Raayan web application. Of 1,239 records screened, 27 studies were included in this review. Adjusted or unadjusted odds ratios (ORs), relative risks, or rate ratios were recorded or calculated. For each risk factor, a qualitative synthesis of low and moderate risk of bias studies classifies the risk factor as definite, likely, unclear, or not a risk factor. For risk factors with sufficiently homogeneous definitions and reference ranges, a quantitative meta-analysis of low and moderate risk of bias studies was implemented to estimate a combined OR. Forty-seven potential risk factors for atonic postpartum hemorrhage were identified in this review, of which 15 were judged definite or likely risk factors. The remaining 32 assessed risk factors showed no association with atonic postpartum hemorrhage or had conflicting or unclear evidence. A substantial proportion of postpartum hemorrhage occurs in the absence of recognized risk factors. Many risk factors for atonic hemorrhage included in current risk-assessment tools were confirmed, with the greatest risk conferred by prior postpartum hemorrhage of any etiology, placenta previa, placental abruption, uterine rupture, and multiple gestation. Novel risk factors not currently included in risk-assessment tools included hypertension, diabetes, and ethnicity. Obesity and magnesium were not associated with atonic postpartum hemorrhage in this review. PROSPERO, CRD42020157521.